Associations of the Force-velocity Profile with Isometric Strength and Neuromuscular Factors - Morales-Artacho, Antonio Jesus; Ramos, Amador García; Pérez-Castilla, Alejandro; Padial, Paulino; Argüelles-Cienfuegos, Javier; de la Fuente, Blanca; Feriche, Belen (International Journal of Sports Medicine, 2018)
We aimed to explore relationships between the force-velocity (FV) profile and the isometric muscle torque performance during a knee extension task. The FV profile (force-intercept [F0], velocity-intercept [V0], maximum power [Pmax], and FV slope) during the countermovement jump (CMJ) exercise and isometric maximum voluntary torque (MVIC) and explosive voluntary torque production were assessed in 43 participants. Electromyography (EMG) was recorded during the isometric assessments and resting muscle architecture measurements were also performed (quadriceps thickness, vastus lateralis pennation angle and fascicle length). Pearson’s correlation coefficients were computed to assess bivariate relationships between the FV profile, isometric torque, EMG activation and muscle architecture. F0 predictions from neuromuscular measurements were assessed through multiple linear regression. Associations of F0 and Pmax with isometric torque increased from explosive to MVIC torque (r≥0.47; P<0.05). Significant associations were found between muscle architecture and F0 and Pmax (r≥0.69; P<0.05), while V0 and FV slope were unrelated (r≤0.27; P>0.05). Quadriceps thickness and VL pennation angle explained ~62% of F0 variance. In conclusion, the knee extensors maximal isometric strength and their morphological architecture are strongly related to F0 estimated from a CMJ FV profile test.
Keywords: force-velocity profile; explosive torque; eate of force development; muscle architecture; electromyography